BIMBINGAN DAN PELATIHAN KONTEN INSTAGRAM SEBAGAI PENERAPAN DIGITAL MARKETING PADA USAHA KECIL DI USAHA KERIPIK BAROKAH KOTA BATU - Rena Feri Wijayanti; Lina Budiarti; Tri Yulistyawati Evelina; Joni Dwi Pribadi (Publisher UPT P2M Politeknik Negeri Malang, 2022)
This activity aims to guide small businesses, especially Keripik Barokah in Batu City. By completing this activity, Keripik Barokah can take advantage and maximize the Instagram platform by presenting content related to the Keripik Barokah or content that is closely related to any information about Keripik Barokah. Through Content uploaded to Instagram, it will provide awareness about products from Barokah Chips and encourage consumers to purchase products in the Batu City area and other cities. The approach used by providing guidance step by step from the first by creating an official Instagram business account from Keripik Barokah, namely @barokahchips_batu, and provides the next step about various examples of creating contents that are possible to be uploaded on a business account. In addition, to maximize the analysis of the use of business Instagram, an explanation of the benefits of Instagram Insight is also given to see the response of account visitors so they can keep up with the increasingly rapid development of digital marketing nowadays.